Micromechanical analysis of orientation dependency on deformation behavior in DP steels by dislocation density-based crystal plasticity simulation. (July 2019) - Jafari, M.; Saeidi, N.; Ziaei-Rad, S.; Jamshidian, M.; Kim, H.S.
Highlights: Constraint imposed by the surrounding hard martensite phases affects the strain distribution within the central ferrite grain. Strain localization was highly affected by the initial orientations of the ferrite grains. Energy absorption capacity for initial orientation [111] of ferrite phase is higher than [001] and random orientations. Shear band formation, evolution and interaction are less probable in the orientations involved with high capacity of stored strain energy. Abstract: Effect of the initial orientations of ferrite grains on the strain localization and consequently deformation behavior in DP780 steels was studied by employing experimental examination and numerical simulations. Based on dislocation density-based crystal plasticity finite element simulation, it was revealed that the initial orientation of ferrite grains plays a key role in the evolution of shear bands and consequently on the ductility of dual phase steels. In other words, the stored dislocation density within each ferrite grain and consequently the energy absorption capacity of DP steels depends on its initial orientation. Moreover, a qualitative comparison between simulated data and measured texture maps exposes the validity of the analysis.